Follow‐up of sustained virological responders with hepatitis C and advanced liver disease after interferon/ribavirin‐free treatment. (1st December 2017) - Kozbial, Karin; Moser, Stephan; Al‐Zoairy, Ramona; Schwarzer, Remy; Datz, Christian; Stauber, Rudolf; Laferl, Hermann; Strasser, Michael; Beinhardt, Sandra; Stättermayer, Albert F.; Gschwantler, Michael; Zoller, Heinz; et al.
Abstract: Background: The introduction of direct‐acting antivirals (DAA) has increased sustained virological response (SVR) rates in patients with advanced liver disease and chronic hepatitis C(CHC)infection. At present, data on clinical outcome and long‐term durability of viral eradication after successful DAA therapy are scarce. Aim: To evaluate the long‐term success of viral eradication in patients with advanced fibrosis or cirrhosis treated with DAAs. Methods: Five hundred and fifty‐one patients with advanced fibrosis (n = 158) or cirrhosis (CPS‐A:317, CPS‐B/C:76) and SVR after interferon and ribavirin‐free DAA therapy treated between October 2013 and April 2016 were studied with a median follow‐up of 65.6 (13.0‐155.3) weeks. Only patients without hepatocellular carcinoma (HCC) at baseline and without liver transplantation were included. Results: Twelve patients (2.2%) died during follow‐up: the mortality rate was 0.6% in F3, 2.2% in CPS‐A and 5.3% in CPS‐B/C patients ( P = .08). During follow‐up 36 patients with cirrhosis (9.1%) developed a liver related event, including 16 with de‐novo HCC (4.1%). Seven patients were transplanted at a median of 9.7 (range 3.8‐21.7) months after EOT. History of decompensation was significantly associated with liver related events during follow‐up (HR 7.9; 95% CI 2.7‐22.6; P < .001), and with mortality (HR 5.5; 95% CI 1.5‐20.2, P = .01). Conclusions: Eradication of HCV by DAA therapy was durable irrespective of the DAA combination used. Most of the cured patients had an excellent long‐term clinical prognosis. Nevertheless, the risk of new occurrence of HCC remains worrisome and thus regular surveillance is obligatory even after clinical stabilization and improvement of the patient.